1995
DOI: 10.1021/ac00116a002
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of IgG Antibody Thermal Stability by Micellar Electrokinetic Capillary Chromatography and Matrix-Assisted Laser Desorption/Ionization Mass Spectrometry

Abstract: Monitoring the stability of immunoglobulin G (IgG) type antibodies is a crucial analytical issue spanning a wide variety of immunological/biotechnological studies, which includes the analysis of conjugated IgG's for drug delivery. Capillary electrophoresis (CE) has proven valuable for the analysis of proteins and has the potential to separate and detect native antibody components. An ideal complement to CE, which is capable of providing the desired detection specificity to provide species identification inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 3 publications
2
60
0
Order By: Relevance
“…However, matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) [7,8], ESI orthogonal-TOF [9,10] and ESI quadrupole [2,[11][12][13] mass spectrometers have been the instruments of choice for MAbs and macromolecules, largely due to the large m/z range of the TOF and high ion transmission efficiency of the quadrupole mass analyzers. Unfortunately, on-line RP-HPLC has not accompanied these previous studies of intact monoclonal antibodies.…”
Section: T He Human Monoclonal Immunoglobulin ␥ (Igg)mentioning
confidence: 99%
“…However, matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) [7,8], ESI orthogonal-TOF [9,10] and ESI quadrupole [2,[11][12][13] mass spectrometers have been the instruments of choice for MAbs and macromolecules, largely due to the large m/z range of the TOF and high ion transmission efficiency of the quadrupole mass analyzers. Unfortunately, on-line RP-HPLC has not accompanied these previous studies of intact monoclonal antibodies.…”
Section: T He Human Monoclonal Immunoglobulin ␥ (Igg)mentioning
confidence: 99%
“…Early examples used MALDI-TOF MS or triple quadrupole instruments for such analyses; [16][17][18] however, the high m/z requirements make such experimental approaches challenging. Currently, analysis of intact proteins is generally in the realm of ESI-TOF-like instruments due to the accessibility of a suitable m/z range, i.e., high m/z, whereby the maximum m/z required is typically 5000 for denatured proteins ( Fig.…”
Section: Mass Spectrometry Of Intact Antibodies Under Denaturing Condmentioning
confidence: 99%
“…Temperature levels at this region, however, are too high for any biological element, such as antibodies, in the biosensor design. An antibody thermal stability study concluded that a heat treatment at 60ºC resulted in the cleavage of the antibody heavy and light chains and promoted the denaturation of the protein (18). For this reason, most biosensor operations are conducted in room temperature (~ 25ºC) (19,20).…”
Section: Conductivity (S/cm)mentioning
confidence: 99%